Idol Worship: How Does It Influence Fan Consumers’ Brand Loyalty? - Chen, Libin; Chen, Guanhong; Ma, Shuxu; Wang, Shuo (Frontiers in Psychology, 2022)
The brand loyalty of fan consumers can be influenced by idol worship if certain celebrity figures are linked with a brand. Collaborating with idols is an effective marketing strategy that many companies use to enhance their appeal to fan consumers and increase their brand equity. Fan consumers demonstrate passion and admiration for their idols, and this psychological phenomenon affects their cognition of brands that are endorsed by their favorite celebrity figures. The purpose of this study was to explore the influence mechanism that propels fan consumers’ brand loyalty and the mediating effects of brand passion and brand attachment. Our results revealed the following key findings: 1) brand personality attraction, perceived emotional value, brand-based self-realization, and relatedness needs satisfaction have a significant effect on brand passion; 2) perceived emotional value and relatedness needs satisfaction have a significant effect on brand passion attachment; 3) brand passion can directly affect brand loyalty, but it also indirectly affects brand loyalty through brand attachment; 4) brand personality appeal, brand-based self-realization, and relatedness needs satisfaction can influence brand attachment through brand passion and ultimately have an impact on brand loyalty; 5) brand perceived emotional value and relatedness needs satisfaction affect brand loyalty through brand attachment. These findings have several implications for enterprises that want to meet fan consumers’ emotional needs, enhance brand loyalty through the use of idol brand endorsement, or implement brand campaigns that involve idols.